ORIENTASI KEWIRAUSAHAAN PADA PEGAWAI YANG MEMASUKI MASA PENSIUN (STUDI KASUS DI KUDUS) - Nurul Rizka Arumsari; Dina Lusianti; Ulva Rizky Mulyani (Value : Jurnal Manajemen dan Akuntansi, 2023)
Preparation for entering retirement (retirement) should have been planned in advance. Especially for people with super active characteristics. This type of employee should have been planning or starting a business for 5 years before entering retirement (retirement) according to their preferred field. The purpose of this work is to analyze the entrepreneurial orientation of employees approaching retirement age in Kudus Regency. The method used in this study is a quantitative method using a survey method using primary data. Information was obtained by distributing questionnaires and a sample of 96 people entering retirement age. The sampling method uses the snowball sampling technique. Data analysis technique using linear multiple regression, t-test, f-test and coefficient of determination. The research results show that risk-taking, competitive aggressiveness and self-control have a positive and significant effect retirement readiness. Meanwhile, innovativeness and activeness have no effect on retirement readiness. Keywords: Entrepreneurial Orientation, Retirement Readiness